Creative Thinking dalam Implementasi dan Rancang Bangun Multiple Sensors berbasis Plug-and-Play Systems with Database - Baskoro, Farid; Suprianto, Bambang; Anifah, Lilik; Ekohariadi; Nurdiansyah, Aristyawan; Rochman, Miftahur (Program Studi Teknik Elektro - Fakultas Teknik - Universitas Widyagama Malang, 2023)
The purpose of this study is to implement creative thinking from the aspect of innovation in developing multiple sensors in plug-and-play system with a database. The method used in this study was an experiment conducted by taking a sample of 5000 data. The location of the research was carried out in the telematics laboratory at Surabaya State University building A8 with room dimensions of 9 x 10 meters. The results of this study indicate a plug-and-play process developed by a scanning process to find connected PORTs without having to do configuration, showing a comparison of the DHT11 error value with a comparator that reaches 2.057 % on the temperature value, 0.829 % on the humidity value, 1.514 % on light intensity value, 1.429% on distance value, and provides 5000 data which includes temperature, humidity, light intensity, and distance data stored in database. Data on temperature, humidity, light intensity, distance, plug-and-play systems, GUI, and databases obtained by researchers are very useful for further research that will be developed to meet smart systems.